1983
DOI: 10.1002/jmv.1890110207
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackie B virus infections in new zealand patients with cardiac and non‐cardiac diseases

Abstract: From 1979 to 1981, a total of 910 cardiac patients and 776 noncardiac patients were studied and compared for evidence of coxsackie B virus infections. Of 78 cardiac patients with coxsackie B infection, 30 had pleurodynia, 18 myocarditis, and 20 pericarditis. The age-adjusted rates of infection per 100 cases of defined category were 7.2, 13.3, and 7.0, respectively. Of 69 noncardiac patients with coxsackie B infection, 27 presented with pyrexia of unknown origin, 14 with upper respiratory tract infection, and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…Coxsackievirus involvement in paediatric myocarditis is clear (see references above as well as [27][28][29]). It has been assumed the CVB also cause the majority of enterovirus-related adult myocarditis, although the data for this rest primarily upon serological studies showing a correlation between higher than expected antibodies against CVB and the presence of heart disease [11,25,26,[30][31][32][33][34][35][36]. While isolation of infectious virus from adult heart tissue has been rare [37][38][39][40], enteroviral involvement in myocarditis has been made clear by the direct detection of enterovirus RNA in heart muscle by nucleic acid hybridisation and RT-PCR [41][42][43]; reviewed in [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Coxsackievirus involvement in paediatric myocarditis is clear (see references above as well as [27][28][29]). It has been assumed the CVB also cause the majority of enterovirus-related adult myocarditis, although the data for this rest primarily upon serological studies showing a correlation between higher than expected antibodies against CVB and the presence of heart disease [11,25,26,[30][31][32][33][34][35][36]. While isolation of infectious virus from adult heart tissue has been rare [37][38][39][40], enteroviral involvement in myocarditis has been made clear by the direct detection of enterovirus RNA in heart muscle by nucleic acid hybridisation and RT-PCR [41][42][43]; reviewed in [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Viruses, bacteria, fungi and parasites are known to induce inflammatory heart disease in humans, although most clinical cases of myocarditis are suspected to be of viral ori gin [1], Among the 20 or more common viruses associated with myocarditis in hu mans [2], indirect serological evidence sug gests the coxsackieviruses group B, serotypes B1-B5, are the major cause of this disease [2][3][4][5][6], These viruses are ubiquitious, by age 30, 18-94% of humans have serologic evi dence of infection to at least one of the CVB serotypes [6][7][8][9], This group of viruses is clas sified within the enterovirus genus of the Picornaviridae family, i.e., they are small nonenveloped RNA genome viruses sur rounded by a protein capsid which does not contain essential glycoproteins or lipids [10], A 'hallmark feature' generally ascribed to the coxsackieviruses group B is that they pro duce lytic infections [10,11], a description which likely originated from studies of the mechanics of virus replication in selected cell lines which yielded high titers of virus while undergoing lysis during the process. However, several reports of nonlytic replica tion of these viruses and long-term persis tence under certain conditions suggest addi tional mechanisms for viral pathology in dis eases with inflammatory cell involvement.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, fulminant hepatitis seems to have been caused by B19 infection following pre‐existing coxsackie B4 infection. Coxsackie B4 virus infection usually causes asymptomatic or self‐limiting febrile illness but occasionally causes myocarditis, meningitis, hepatitis and fever of unknown origin (Lau, 1983). Experimental intranasal B19 infection in adult volunteers has confirmed that viraemia appears from 7 to 10 d after infection and continues for another 7 d (Anderson et al , 1985), indicating that the B19 infection in this case may have occurred during the last 10 d of January.…”
Section: Discussionmentioning
confidence: 99%